Gastrointestinal parasites of swine raised in different management systems in the State of Rio de Janeiro, Brazil - Alynne S. Barbosa; Otilio M.P. Bastos; Laís V. Dib; Mayara P. de Siqueira; Matheus L. Cardozo; Luiz Claudio Ferreira; William T. Chaves; Ana Beatriz M. Fonseca; Claudia M.A. Uchôa; Maria Regina R. Amendoeira (Pesquisa Veterinária Brasileira, 2015)
Abstract: From 2012 to 2013 were surveyed gastrointestinal parasites from pig farms located in different municpaliyies in the state of Rio de Janeiro. Fecal samples from 790 pigs were collected from the rectum on 88 family farms and 702 farms with industrial production. The samples were subjected to Faust et al., Sheather, Ritchie, Lutz and direct examination faecal techniques. The estimated parasite prevalence was 93.1% in family farms and 59.1% in industrial farms. Balantidium coli, coccidia and Entamoeba sp. were the parasites with the highest frequencies, and the male and female reproductive categories and fatteners pigs the most infected (p<0.05). Trophozoites of B. coli were most evident in stool samples from semi-solid followed by solid and diarrheal consistencies. Strongyles eggs and Trichuris suis have been detected exclusively in family farms. Ascaris suum eggs and Strongyloides ransomi showed low frequency. The high degree of parasitism, especially protozoa, indicates the need to reassess the management of pigs in both types of production.